Gettysburg - Maxwell, Ronald F.; Ehlers, Corky; Edelman, Randy; Berenger, Tom 1950-; Daniels, Jeff 1955-; Sheen, Martin; Caulfield, Maxwell; Conway, Kevin; Howell, C. Thomas; Jordan, Richard; Lancester, James; Lang, Stephen; et al.
Civil War drama depicting the events and personal struggles of the Union and Confederate soldiers at the Battle of Gettysburg.